Introducing a gamification element in enterprise collaboration platforms: Only a flash in the pan or a lasting effect? - Stojko, Laura; Lin, Lin; Soucek, Roman; Moser, Klaus; Koch, Michael (ECSCW 2024 Exploratory Papers and Notes, 2024)
Enterprise collaboration platforms are expected to facilitate effective information exchange by supporting employee sociability, i.e., finding communication partners and building common ground. However, they often suffer from low user engagement requiring the implementation of additional design elements to encourage user participation. Though previous research found evidence for the effectiveness of introducing new features, in particular gamification elements, to such platforms, the question remains whether it represents more than a flash in the pan and creates some sustainable effects over time. Therefore, the current longitudinal quasi-experimental field study investigates the effectiveness of introducing one exemplary gamification element, a progress bar to encourage profile completion, as a new feature within a digital collaboration platform in a large public sector organization across time. We collected data before (t1 – t3) and after (t4 – t6) implementation of the progress bar. We analyzed the data using linear mixed-effects models, enabling the assessment of time effects and interaction effects of time and progress bar implementation. In fact, profile completion rates increases over time, and introducing a progress bar significantly impacted users’ profile completion behavior. More importantly, we found both short-term effects and, after an interim decline, a sustainable change in user behavior after the progress bar implementation over time. Thus, this study presents quantitative evidence of the long-term effectiveness of introducing a gamification element in enterprise collaboration platforms over time.<br
Keywords: enterprise collaboration platforms; user profiles; profile completion; gamification; mixed-effects